2015
DOI: 10.1016/j.hgmx.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cancer mortality in Mexico: 1990–2012

Abstract: Introduction: Cancer is the leading cause of death worldwide, with 8.2 million deaths in 2012: 4.7 million (57%) male deaths and 3.5 million (43%) female deaths. In Mexico, it ranks second as a cause of death (2007). Objective: To describe the most common types of cancers, as well as their trends over the 1990---2012 period. Methods: Mortality rates were standardised (ASMR) by age and gender. The annual percent change (APC) was calculated using Poisson regression model and by means of analysing time trends and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…5 In spite of the relative importance of LC in terms of incidence, previous literature has shown that the mortality rate from LC has decreased in the lasts two decades, particularly among men. [6][7][8][9] Although a reduction in mortality has been documented previously, it is important to note other health metrics related to the burden imposed by LC and to highlight geographic patterns. In particular, the Global Burden of Disease Study (GBD-2016) offers estimates of the burden of LC based on its impact on premature mortality and time lived with disability summarized in the number of Disability-Adjusted Life Years (DALYs).…”
Section: Introductionmentioning
confidence: 87%
“…5 In spite of the relative importance of LC in terms of incidence, previous literature has shown that the mortality rate from LC has decreased in the lasts two decades, particularly among men. [6][7][8][9] Although a reduction in mortality has been documented previously, it is important to note other health metrics related to the burden imposed by LC and to highlight geographic patterns. In particular, the Global Burden of Disease Study (GBD-2016) offers estimates of the burden of LC based on its impact on premature mortality and time lived with disability summarized in the number of Disability-Adjusted Life Years (DALYs).…”
Section: Introductionmentioning
confidence: 87%